RESEARCH ON THE TECHNOLOGY OF PRODUCING FOOD PRODUCTS ENRICHED WITH ESSENTIAL FATTY ACIDS BASED ON CEREAL PRODUCTS (International journal of artificial intelligence, 2025)
This article discusses the scientific study of the technology of producing food products enriched with essential fatty acids based on cereals. The study analyzed the chemical composition of cereals, their components beneficial to human health, and methods of enrichment with omega-3 and omega-6 fatty acids. Also, the technological stages used in the enrichment process, ways to increase the nutritional and biological value of the product, and factors affecting the shelf life were studied on a scientific basis. Based on the results obtained, an effective technological model for the production of cereals as functional foods was developed. This study is of significant scientific and practical importance in ensuring food safety, establishing a healthy diet for the population, and creating a new generation of bioactive products.